The Comprehension of the Nichar Community for the Development and Growth of the Destination as a Creative Tourism Destination? - Vikesh Kashyap; Ashutosh Sharma; Himanshu Katoch; Rohit Bisht (Centre For Tourism Planning and Development, 2023)
The emerging concept in culture tourism is creative tourism, which allows visitors to grasp themselves in local traditions and culture. It is a way that can be utilized for the growth and development of communities. Creative Tourism can be seen as means of promoting prosperity and well-being in different countries. Although, (UNESCO, 2017) assessed the alteration of cultural tourism into creative tourism as it addresses more to the Sustainable Development Goals. The Structured Questionnaire was formed and a survey was conducted and 50 samples from each village were collected from for analysis and interpretation. To exert the influence, this research paper has been designed to pertain the scope of creative tourism resources and to understand community willingness, awareness, and perception of the development and growth of tourism in the prospect of creative tourism destination. It has been unearthed that three villages (Puja, Garode, and Kashpo) in Himachal Pradesh's Kinnaur region require consciousness for creative tourism implementation. The residents with high education qualifications have shown a positive approach. The state of Himachal Pradesh is well notable of its community hidden treasure and represents it as a creative place making although it doesn’t have any region that represents itself as a creative tourism destination.